Influence Of Hr Competence, Utilization Of Information Technology And Understanding Of Accounting Standards On The Quality Of LPD Financial Statements In UBUD District - Ni Kadek Selvi Dwi OKTAPIYANTI; Ida Idam Manik SASTRI; AA Putu Agung Mirah Purnama SARI (Indonesia Strategic Sustainability, 2022)
This study aims to empirically test the Influence of Human Resource Competence, Utilization of Information Technology and Understanding of Accounting Standards on the Quality of Financial Reports. Sample selection was taken by using the purposive sampling method. The data used is secondary data. The population in this study were employees in the finance department in all LPDs in Ubud sub-district, with a total of 32 LPDs. Determining the sample adopted the purposive sampling technique, namely selecting samples based on criteria so that the research sample was 96 samples obtained from the total population multiplied by the year of observation. The data analysis used in this study was a multiple linear regression analysis with a significance level of 5%. The results show that the tax audit has a positive and significant effect on individual tax revenues. Tax collection has a positive and significant effect on individual tax revenues. Tax socialization has a positive and significant effect on individual tax revenues. Suggestions for companies are expected to continue to improve the implementation of audits, tax collection and socialization of taxation. For further research, it is expected to use other variables such as ownership of NPWP.